Ideal Convergence of k-Positive Linear Operators - Akif Gadjiev; Oktay Duman; A. M. Ghorbanalizadeh (Journal of Function Spaces and Applications)
We study some ideal convergence results of k-positive linear operators defined on an appropriate subspace of the space of all analytic functions on a bounded simply connected domain in the complex plane. We also show that our approximation results with respect to ideal convergence are more general than the classical ones.